2020
DOI: 10.7150/ijbs.45221
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards COVID-19 among Chinese residents during the rapid rise period of the COVID-19 outbreak: a quick online cross-sectional survey

Abstract: Unprecedented measures have been adopted to control the rapid spread of the ongoing COVID-19 epidemic in China. People's adherence to control measures is affected by their knowledge, attitudes, and practices (KAP) towards COVID-19. In this study, we investigated Chinese residents' KAP towards COVID-19 during the rapid rise period of the outbreak. An online sample of Chinese residents was successfully recruited via the authors' networks with residents and popular media in Hubei, China. A self-developed online K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

790
2,988
213
186

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 2,645 publications
(4,177 citation statements)
references
References 10 publications
790
2,988
213
186
Order By: Relevance
“…Approximately eight weeks after the first diagnosis in China, the mean knowledge score for a sample of Chinese citizens was 10.8/12 (approximately 90%) 14 and it was suggested that the knowledge of Chinese citizens is high because of their experiences with the SARS outbreak in the early 2000s, and the observation that this sample was relatively affluent and highly educated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Approximately eight weeks after the first diagnosis in China, the mean knowledge score for a sample of Chinese citizens was 10.8/12 (approximately 90%) 14 and it was suggested that the knowledge of Chinese citizens is high because of their experiences with the SARS outbreak in the early 2000s, and the observation that this sample was relatively affluent and highly educated.…”
Section: Discussionmentioning
confidence: 99%
“…In this sample nearly 30% of people reported attending gatherings or going to places with more than 50 people in the previous five days, contrary to advice from the CDC since March 12, 2020 (survey conducted on March 17, 2020). In China, only 3.6% of people reported going to crowded places in the previous two weeks 14 . It is possible that the coordinated effort from, as well as the unchecked authority by, the Chinese government, to lockdown provinces provided most of the motivation for Chinese citizens to obey these mandates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations